Constraints in Contract and Non-Contract Broiler Farming Systems in Eastern Plain Zone of Uttar Pradesh - Singh, Amit Kumar; Sagar, M.P.; Chander , Mahesh (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study was conducted with the objective to identify the constraints faced by poultry farmers under contract and non-contract broiler farming systems in four randomly selected blocks of Azamgarh and Varanasi districts of Uttar Pradesh. The results revealed that major constraints faced by contract broiler farmers were delay in providing chicks (46.67%), low growing charges by the Integrators (35%), delay in lifting produce (28.33%) and delay in providing veterinary services (21.67%). Whereas non-contract broiler farmers were affected by marketing related problems. The major constraints faced by them were price fluctuations (96.67%), lack of cooperative marketing societies (93.33%), no supporting price policy (85%) and unsatisfactory price of produce (83.33%).